2005
DOI: 10.1007/s10433-005-0013-x
|View full text |Cite
|
Sign up to set email alerts
|

Who retires early and why? Determinants of early retirement pension among Danish employees 57–62 years

Abstract: The aim of this study was to identify demographic characteristics and occupational determinants of transition from employment to voluntary early retirement pension (ERP). A questionnaire-based survey among 365 employees in Denmark 57-62 years was performed in 2000, with a register-based follow-up 4 years later. Early retirement was associated with increasing age, and lower socioeconomic position. There were weak associations between gender and ERP. Low skill discretion, high conflict in work and two measures o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
92
0
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(103 citation statements)
references
References 20 publications
7
92
0
4
Order By: Relevance
“…The predictors we found are generally in line with previous research. Younger age was a predictor of having paid work, which is in line with previous findings in studies on (early) retirement [29,35]. Working more hours per week at baseline was associated with having paid work at follow-up as well.…”
Section: Predictors For Having Paid Work In Older Workerssupporting
confidence: 90%
See 2 more Smart Citations
“…The predictors we found are generally in line with previous research. Younger age was a predictor of having paid work, which is in line with previous findings in studies on (early) retirement [29,35]. Working more hours per week at baseline was associated with having paid work at follow-up as well.…”
Section: Predictors For Having Paid Work In Older Workerssupporting
confidence: 90%
“…The relation between having high physical work demands at baseline and having paid work at follow-up was found to be significantly different between the groups of workers with and without chronic disease. Previous studies on workers in general have shown that high physical workload was associated with early retirement [28,29]. In a study in workers suffering from various chronic diseases, physical workload was associated with exit from the workforce because of work disability [30].…”
Section: Differences and Similarities Between Workers With And Withoumentioning
confidence: 97%
See 1 more Smart Citation
“…A significant relationship between work-status and work satisfaction was expected, as previous studies have found that early retirement is related to working conditions, which can be assumed to be related to work satisfaction. Lund and Villadsen (2004) have found that high conflict in work and uncomfortable work positions increases the risk for early retirement and also monotonous work-environments, with exposure to chemicals, hard physical demands and stressful environments, have been shown to increase the risk for early retirement (Kilbom et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Solem (1997) found that a low professional training was related to an early exit from work and Lund and Villadsen (2004) have found a relationship between low socioeconomic status, as well as low skill discretion and early retirement. Thus, the power of the measurements of education and economy in the present study could be questioned.…”
Section: A-group B-groupmentioning
confidence: 99%